Incidence of pemphigoid diseases in Northern Germany in 2016 – first data from the Schleswig‐Holstein Registry of Autoimmune Bullous Diseases. (10th February 2021) - van Beek, N.; Weidinger, A.; Schneider, S.W.; Kleinheinz, A.; Gläser, R.; Holtsche, M.M.; von Georg, A.; Hammers, C.M.; Hübner, F.; Lima, A.‐L.; Gola, D.; Sadik, C.D.; et al.
Abstract: Background: Autoimmune bullous diseases (AIBD) are rare disorders characterized by autoantibody formation against components of adhesion molecules; in pemphigoid diseases (PD), these are proteins of hemidesmosomes and basement membrane, important for cell‐matrix adhesion in skin and/or mucous membranes. Incidences of these diseases vary considerably between different populations. Objectives: To establish a registry prospectively recruiting all AIBD patients in a geographically well‐defined region in Northern Germany (Schleswig‐Holstein). Methods: Only patients with verified disease (by clinical presentation, histology, direct and/or indirect immunofluorescence and /or ELISA) living in Schleswig‐Holstein were included. Incidences of PD were estimated based on the total number of inhabitants in Schleswig‐Holstein, stratified by birth year and sex. Results: Of 67 patients with PD [35 male, 32 female, mean age 75 (standard deviation 14.3 years)], 83% were patients with bullous pemphigoid [ n = 56, 28 male, 28 female, mean age 78 (SD 9.9)]. The resulting crude incidences were 23.4 patients/million/year for all pemphigoid patients, 19.6 patients/million/year for bullous pemphigoid (age‐standardized 16.9 patients/million/year) with a strong increase in bullous pemphigoid patients in the age group of 85–90 years with 262 patients/million/year. Incidences for bullous pemphigoid were higher in urban compared to rural areas. Other PD (mucous membrane pemphigoid, linear IgA disease, anti‐p200 pemphigoid) were less frequent with crude incidences of 2.1, 1.0 and 0.7 patients/million/year, respectively. Conclusions: This study prospectively analyses the incidence of PD in a carefully defined geographical area. The highest incidence among PD patients was found for bullous pemphigoid. The incidence of bullous pemphigoid is considerably increased compared to previous reports and reveals regional differences. Further studies are needed in order to clarify these findings.